Highly Ordered Mesoporous NiCo2O4 as a High Performance Anode Material for Li-Ion Batteries - Ren, Qilong; Wu, Guangyu; Xing, Weinan; Han, Jiangang; Li, Pingping; Li, Bo; Cheng, Junye; Wu, Shuilin; Zou, Rujia; Hu, Junqing (Frontiers in Chemistry, 2019)
The controlled synthesis of highly ordered mesoporous structure has attracted considerable attentionin the field of electrochemistry because of high specific surface areawhich can contribute the transportation of ions. Herein, a general nano-casting approach is proposed for synthesizing highly ordered mesoporous NiCo2O4 microspheres. The as-synthesized mesoporous NiCo2O4 microsphere materials with high Brunner-Emmett-Teller (BET) surface area ( 97.77 m2g-1) and uniform pore size distribution around 4 nm exhibited a high initial discharge capacity of 1467 mAhg-1, a good rate capability as well as cycling stability. The superior electrochemical performance was mainly because of its highly porous nature of NiCo2O4, which rendered volume expansion during the process of cycling and shortened lithium-ions transport pathways. These properties showcase the inherent potential for use of highly ordered mesoporous NiCo2O4 microspheres as a potential anode materials for lithium-ion batteries in the future.